PENGKAJIAN IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR DAN MADRASAH ffiTIDAIYAH DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Suryono, Yoyon; Raharja, Setya (Jurnal Cakrawala Pendidikan, 2016)
This article is based on a research with a diagnostic evaluation survey approach conducted to obtain a description of the implementation of the school-based management (SBM) at Islamic primary schools and primary schools with no special religious affiliation in the Yogyakarta Special Priovince. with the Yogyakarta Municipality and the Sleman and Kulon Progo Regencies. represented respectively by the Gondokusuman. Depok. and Wates Subdistricts. taken as regional samples and eight state and four private Islamic and non-religiously-affilalted primary schools taken as school samples. Respondents at the school level consist of the schools' principals. teachers. and students' parents while those at the subdictrict level consist ofschool inspectors, prominent community figures. and representatives of subdistrict governing bodies. professional organizations. and the Department of Religions. The data are collected by means of a questionnaire about the schools' condition and implementation of the SBM and analyzed in a descriptive-quantitative way. The results indicate that the SBM has started to be implemented though still with the support ofminimum managerial capability and comprehension. The lack of managerial capability is apparent in the aspects of designing. coordinating, implementing, and evaluating the plan or program conducted at school. The SBM at the state and private Islamic and non-religiously-affiliated primary schools needs to keep being implemented to improve school performance and quality and evenly distribute education, with some improvements in the concept and implementation. Clearness or clarification of the concept is necessary to integrate regional autonomy, decentralization of education, and the SBM At the level ofimplementation there need to be improvements in the mastery ofthe aspects ofthe SBM which at the moment are still inaccurately understood